Learning by exploring: How much guidance is optimal?. (August 2019) - Newman, Phillip M.; DeCaro, Marci S.
Abstract: Exploring a new concept before instruction can benefit conceptual understanding, but is demanding. The current experiments examined whether providing guidance during exploration improves learning. Undergraduate students explored the procedures and concept of statistical variance prior to direct instruction. In Experiment 1 ( N = 123), exploring using worked examples (full guidance) led to higher posttest scores than exploring using an invention activity (no guidance) or completion problems (partial guidance). In contrast, Experiment 2 ( N = 190) found no learning benefit of exploring using worked examples compared to inventing. Overall, exploring improved learning compared to instruct-then-practice conditions. Experiment 3 ( N = 147) demonstrated that exploring worked examples improved learning compared to exploring using an invention activity—but only when preceded by a pretest. Students' reported cognitive load, knowledge gaps, and interest were also assessed. Findings suggest that combining a pretest with worked examples helps students perceive knowledge gaps and discern problem features, maximizing exploration while reducing cognitive load. Highlights: Exploring problems before instruction benefits understanding but is demanding. Exploring with worked examples improved learning compared to inventing solutions. This benefit only occurred when worked examples were preceded by a pretest. Exploration activities should increase knowledge gaps but reduce cognitive load.